2017
DOI: 10.1093/cid/cix367
|View full text |Cite
|
Sign up to set email alerts
|

Co-trimoxazole Prophylaxis, Asymptomatic Malaria Parasitemia, and Infectious Morbidity in Human Immunodeficiency Virus–Exposed, Uninfected Infants in Malawi: The BAN Study

Abstract: CPT may have an important role to play in reducing the leading global causes of morbidity and mortality in the growing population of HEIs in malaria-endemic resource-limited settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The use of cotrimoxazole has been associated with a lower risk of malaria in children, pregnant women, or severely immunocompromised patients; its discontinuation also increases malaria prevalence and parasitemia [6,15,19,31]. In this study, the prevalence of malaria among participants who were not under CTX prophylaxis was twofold higher than those from individuals who were under otrimoxazole prophylaxis (8.3% vs. 4.1%).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The use of cotrimoxazole has been associated with a lower risk of malaria in children, pregnant women, or severely immunocompromised patients; its discontinuation also increases malaria prevalence and parasitemia [6,15,19,31]. In this study, the prevalence of malaria among participants who were not under CTX prophylaxis was twofold higher than those from individuals who were under otrimoxazole prophylaxis (8.3% vs. 4.1%).…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, there were more patients under CTX in the PLHIV group with no malaria than in the P. falciparum-infected PLHIV group. Recently, this sulfa combination drug was recommended to all PLHIV living in malaria endemic countries due to its recognized activity against protozoal parasites, more precisely the Plasmodium species [19,20,32]. This recommendation was not established in Gabon at the time of the study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CPT for participants in the BAN study was implemented in June 2006. Several analyses, using data from the BAN study and from other studies, have shown CPT to be associated with reduced subclinical malaria ( 23 ), lower rates of illness and death caused by infectious diseases ( 24 26 ), and reduced incidence of severe anemia ( 27 ). The antibacterial properties of cotrimoxazole are probably the cause of the observed association between CPT and reduced overall antibacterial prescriptions.…”
Section: Discussionmentioning
confidence: 99%